2018
DOI: 10.5435/jaaos-d-17-00198
|View full text |Cite
|
Sign up to set email alerts
|

Complications After Pelvic Arteriography in Patients With Pelvic Ring Disruptions

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In our cohort, the patients who underwent pelvic arterial embolisation (PAE) showed the worst outcomes in terms of number of surgical procedures required to control SSI and hospitalisation. Arterial embolisation represents an efficient acute intervention to control severe arterial bleeding following pelvic trauma [ 10 ] but potential complications include: gluteal muscle necrosis and skin ulceration, although these are reported to be rare in the literature [ 10 , 52 ]. Manson et al recently reported an increase of deep infection rate after acetabular fracture fixation (up to 58% of cases) in patients who previously underwent pelvic angiographic embolisation.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, the patients who underwent pelvic arterial embolisation (PAE) showed the worst outcomes in terms of number of surgical procedures required to control SSI and hospitalisation. Arterial embolisation represents an efficient acute intervention to control severe arterial bleeding following pelvic trauma [ 10 ] but potential complications include: gluteal muscle necrosis and skin ulceration, although these are reported to be rare in the literature [ 10 , 52 ]. Manson et al recently reported an increase of deep infection rate after acetabular fracture fixation (up to 58% of cases) in patients who previously underwent pelvic angiographic embolisation.…”
Section: Discussionmentioning
confidence: 99%
“…Localization of potential arterial injury during pelvic ring fractures can aid in the selective angiography performed during primary treatment of a polytraumatized patient by means of embolizing the bleeding artery (Tosounidis and Giannoudis, 2013;Lustenberger et al, 2015;Scemama et al, 2015;Rudloff and Triantafillou, 2016;Comai et al, 2016;Wiley et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Angiography, however, carries a 20% risk of serious complications that include gluteal necrosis leading to hip disarticulation or hemipelvectomy. 11 In addition, timing remains an issue with the Baltimore group reporting time to embolization being more than 5 hours and potentially contributing to the 80% of deaths attributed to acute exsanguination. 12 Beyond the data that we present, success of our protocol to achieve a reduction in mortality from acute exsanguination relies on the intangible concepts of team and culture.…”
Section: Combine Reducing Pelvic Volumementioning
confidence: 99%
“…Angiography, however, carries a 20% risk of serious complications that include gluteal necrosis leading to hip disarticulation or hemipelvectomy. 11 In addition, timing remains an issue with the Baltimore group reporting time to embolization being more than 5 hours and potentially contributing to the 80% of deaths attributed to acute exsanguination. 12…”
mentioning
confidence: 99%